A high-quality marble replica ceramic glaze and preparation method thereof
Through the specific replica dry particles and replica glaze slurry formula, combined with the use of modified calcined zinc oxide and modified glass sand, the problem of difficult to show texture and touch of existing marble tiles is solved, and the preparation of high-quality marble replica ceramic glaze is achieved.
Patent Information
- Application Number
- CN202411242726.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-05
AI Technical Summary
Existing marble tiles are difficult to effectively express the texture and touch of marble, resulting in a smooth and lack of texture on the tiles.
Using specific replica dry particles and replica glaze slurry formulas, the use of modified calcined zinc oxide and modified glass sand combined with high temperature melting and ball milling treatment is formed to form a high-quality marble replica ceramic glaze.
The gloss of the ceramic surface is improved, and the patina texture and texture layer of the replica marble glaze layer is maintained, and a high-quality marble replica ceramic is obtained.
Smart Images

Figure BDA0005029768350000111 
Figure BDA0005029768350000121 
Figure BDA0005029768350000122
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic glazes and relates to a high-quality marble replica ceramic glaze and a preparation method thereof. Background Art
[0002] Ceramics is one of the synonyms of Chinese culture. Ceramics have a long history of development and come in many varieties. Good ceramic products are inseparable from good ceramic glazes. Ceramic glaze refers to a glaze slurry made from specific mineral raw materials in a certain proportion, applied to the surface of the blank, and calcined at a certain temperature. It finally becomes a thin layer of glass covering the surface of the ceramic product, which has the function of protecting the ceramic products and beautifying them.
[0003] Ceramic glazes can give ceramic products different texture patterns. For ceramic tiles, marble patterns are widely used, but current marble tiles only use screen printing lines combined with inkjet to reflect the marble texture effect. The resulting tile surface is flat and smooth, which cannot well show the texture and touch of marble. The marble effect of tiles needs to be improved. Summary of the invention
[0004] The purpose of the present invention is to provide a high-quality marble replica ceramic glaze and a preparation method thereof. The replica ceramic glaze prepared in the present invention can improve the surface condition of the ceramic, has good glossiness, and can stably maintain the patina texture and texture layering produced by the replica marble glaze layer, thereby obtaining a high-quality marble replica ceramic.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-quality marble replica ceramic glaze, comprising replica dry particles and replica glaze slurry in a mass ratio of 1:(0.6-0.8), wherein the replica glaze slurry is prepared by mixing the replica slurry with water;
[0007] The replica slurry comprises the following raw materials in parts by weight: 20 to 25 parts of potassium feldspar, 2 to 5 parts of talc, 15 to 25 parts of calcined kaolin, 8 to 13 parts of modified calcined zinc oxide, 16 to 21 parts of barium carbonate, 5 to 10 parts of nepheline, 3 to 6 parts of dolomite, and 1 to 3 parts of fluorite;
[0008] The replica dry particles include the following raw materials in parts by weight: 14 to 18 parts of aluminum oxide, 50 to 53 parts of silicon dioxide, 3 to 7 parts of calcium oxide, 2 to 5 parts of magnesium oxide, 0.5 to 1.5 parts of potassium oxide, 3 to 5 parts of sodium oxide, 1 to 2 parts of boron oxide, 4 to 7 parts of barium oxide, 6 to 8 parts of strontium oxide, and 0.5 to 1 part of calcium fluoride;
[0009] The preparation process of the modified calcined zinc oxide is as follows:
[0010] S11, by weight, adding 30 to 40 parts of calcined zinc oxide and 20 to 30 parts of lithium silicate to 80 to 100 parts of deionized water and mixing them evenly to obtain a suspension;
[0011] S12, drying the suspension at 100-110° C., adding 20-30 parts of aluminum silicate and grinding thoroughly to obtain crude zinc oxide;
[0012] S13, adding 20 to 33 parts of crude zinc oxide, 2 to 5 parts of cationic starch, and 2 to 4 parts of silane coupling agent to 40 to 60 parts of deionized water, subjecting to ultrasonic treatment at 400 to 600 W for 1.5 to 3 hours, filtering, and drying to prepare pretreated zinc oxide;
[0013] S14, mixing the pretreated zinc oxide and modified glass sand in a mass ratio of (4-5.5):1, putting them into a ball mill for grinding, the ball mill speed is 300r / min, the grinding time is 3h, and modified calcined zinc oxide is obtained.
[0014] As a preferred technical solution of the present invention, the mass ratio of the replica slurry to water is 1:(1.8-2.3).
[0015] As a preferred technical solution of the present invention, the preparation process of the modified glass sand is as follows:
[0016] S31, washing the glass sand with anhydrous ethanol and drying it in a vacuum drying oven at 100°C, and then preheating it to 60-70°C;
[0017] S32, in parts by weight, adding 5 to 10 parts of glass sand and 2 to 4 parts of dispersant to 75 to 100 parts of deionized water, stirring to obtain a mixed slurry, heating to 80 to 90° C., adjusting the pH value of the mixed slurry to 8 to 9 with alkali, adding 5 to 10 parts of cerium sulfate, stirring and aging for 1 to 2 hours, continuing to add alkali to adjust the pH value of the mixed slurry to 8 to 10, maintaining the temperature for aging for 1 to 3 hours, filtering, washing, and drying to obtain a solid;
[0018] S33, sintering the solid at 400-600°C for 3-5h to obtain cerium oxide-coated glass sand, and then crushing the solid to obtain modified glass sand.
[0019] As a preferred technical solution of the present invention, in step S13, the silane coupling agent is one of KH550, KH560 or KH570.
[0020] As a preferred technical solution of the present invention, in step S32, the dispersant is one of carboxymethyl cellulose and calcium dodecyl sulfate.
[0021] As a preferred technical solution of the present invention, in step S32, the alkali is sodium hydroxide or potassium hydroxide.
[0022] A method for preparing a high-quality marble replica ceramic glaze comprises the following steps:
[0023] S71. According to the weight ratio of the dry granule formula, the components are fully mixed and put into a ball mill, and ground at a speed of 400-500 r / min for 1-2 hours, and then 0.5-1 parts of sodium tripolyphosphate and 0.5-1 parts of sodium silicate are added, and the speed is maintained and the grinding is continued for 6-8 hours, and the dry granule mixture is prepared by sieving;
[0024] S72, heating the dry granule mixture at 1500-1600° C. to melt, then naturally cooling to room temperature, and crushing to a fineness of 350-450 meshes to obtain replica dry granules;
[0025] S73, mixing the raw materials of the replica slurry according to the formula ratio, grinding them fully in a ball mill at a speed of 400-500 r / min for 2-3 hours, and then adding water to obtain a replica glaze slurry;
[0026] S74, under nitrogen conditions, fully and uniformly stir the replica glaze slurry and the replica dry particles according to the mass ratio to obtain a mixed slurry;
[0027] S75, filtering the mixed slurry and introducing it into a ball mill for wet grinding and ball milling to prepare the high-quality marble replica ceramic glaze.
[0028] As a preferred technical solution of the present invention, in step S74, the rotation speed of the sufficient stirring is 500-600 r / min, and the stirring time is 25-35 min.
[0029] As a preferred technical solution of the present invention, in step S75, the wet ball milling time is 50 to 100 minutes.
[0030] The tiny particles of glass sand can fill the tiny pores in the replica ceramic glaze to make the glaze surface smoother. The present invention obtains glass sand with cerium oxide coated on the surface by mixing glass sand with water-soluble cerium salt, aging in an alkaline environment and then sintering. Cerium oxide can promote the growth of crystals in the ceramic glaze layer. When the surface of the glass sand is coated with cerium oxide, these glass sand particles can fill the pores in the replica dry particle melting process, and can also promote the formation of fine and uniform crystals in the glaze layer with the help of the cerium oxide on the surface. This uniform crystal structure can make light reflect on the glaze surface. When the glass sand is coated with cerium oxide, it will present a more uniform and smooth effect, thereby improving the glossiness of the glaze, thereby improving the quality of the glaze and making it closer to the natural texture of marble; and when the surface of the glass sand is coated with cerium oxide, these cerium oxide particles will participate in the formation of the glass phase during the melting process of the glaze, improve the degree of vitrification of the glaze layer, enhance the flatness and smoothness of the glaze surface, and further improve the glossiness of the glaze; because cerium oxide is evenly distributed in the glaze, it can avoid the situation where the glaze surface has large local glossiness differences, making the overall glaze surface present a more harmonious and unified gloss effect. Because the surface of the glass sand is coated with cerium oxide, the interaction between cerium oxide and glass sand can form a stronger bonding force, which can help the ceramic glaze to be more firmly attached to the ceramic substrate when it is prepared into a ceramic glaze layer, thereby maintaining the glaze texture and the realistic effect of marble.
[0031] In the present invention, calcined zinc oxide is modified, soluble lithium silicate is loaded onto the surface of zinc oxide by a solution impregnation method and is evenly mixed by grinding, and then aluminum silicate is added and ground, so that the three can be mixed more fully, and aluminum silicate has good adhesion, which can make the three more closely combined, reduce the occurrence of agglomeration, improve the uniformity and stability of the glaze, increase the bonding force between zinc oxide and the glaze matrix, so that the glaze layer is more firmly attached to the ceramic matrix; zinc oxide can better play the role of increasing gloss, and at the same time can improve the melting behavior and crystallinity of the glaze in the melting process, help reduce glaze defects, and improve the overall quality of the glaze.
[0032] Treating the crude zinc oxide with a silane coupling agent can form an organic-inorganic hybrid layer on the surface, thereby enhancing the compatibility of zinc oxide with other ingredients, and at the same time improving the dispersion state of zinc oxide, reducing the agglomeration and pores between glaze particles, making the surface smoother, reducing surface roughness, and helping to improve surface gloss; fully mixing the zinc oxide treated with a silane coupling agent with modified glass sand by grinding helps to evenly coat the glaze on the ceramic surface, reduce pores and defects in the glaze layer, and at the same time, mixing with modified glass sand can change the surface properties of zinc oxide, so that it can better reflect light, thereby increasing the gloss of the glaze, promoting the formation of microcrystalline structure in the glaze layer, and improving the gloss and brightness of the glaze surface; zinc oxide has a coloring effect in the glaze, which can enhance the blue hue of the glaze and weaken other wavelengths of light. The modification of glass sand further adjusts and optimizes this coloring effect, making the color of the glaze more vivid and uniform.
[0033] Beneficial effects of the present invention:
[0034] By adopting specific replica dry particle components and combining them with a higher melting temperature, the crystallization degree of the marble glaze layer is improved, the glossiness is improved, and a ceramic glaze layer with better surface performance is obtained. By using modified calcined zinc oxide in the ceramic glaze slurry, together with kaolin and barium carbonate, the surface flatness and brightness of the glaze layer are improved, and fluorite and other ingredients are used to improve the surface glossiness and texture. By first mixing the replica dry particles and ball-milling them, then melting them at a high temperature, and then mixing them with the replica glaze slurry that has been ball-milled, the full combination of the replica glaze slurry and the replica dry particles is promoted, the coordination effect of the replica glaze slurry and the replica dry particles is better exerted, and the texture and surface performance of the glaze layer are improved.
[0035] The replica ceramic glaze prepared in the present invention can improve the surface condition of ceramics, so that the replica marble glaze layer has a crystallized, soft and delicate crystalline texture. By controlling the ratio of replica dry particles to replica glaze slurry, the surface glossiness and flatness of the glaze layer are more inclined to the texture effect of marble, thereby stably maintaining the patina texture and texture layering produced by the replica marble glaze layer. DETAILED DESCRIPTION
[0036] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0037] Example 1
[0038] Preparation of modified glass sand:
[0039] S31, washing the glass sand with anhydrous ethanol and drying it in a vacuum drying oven at 100°C, and then preheating it to 60°C;
[0040] S32, in parts by weight, adding 5 parts of glass sand and 2 parts of carboxymethyl cellulose to 75 parts of deionized water, stirring to obtain a mixed slurry, heating to 80° C., adjusting the pH value of the mixed slurry to 8 with sodium hydroxide, adding 5 parts of cerium sulfate, stirring and aging for 1 hour, continuing to add sodium hydroxide to adjust the pH value of the mixed slurry to 8, maintaining the temperature for aging for 1 hour, filtering, washing, and drying to obtain a solid;
[0041] S33, sintering the solid at 400°C for 3 hours to obtain cerium oxide-coated glass sand, and then crushing the solid to obtain modified glass sand.
[0042] Preparation of modified calcined zinc oxide:
[0043] S11, by weight, adding 30 parts of calcined zinc oxide and 20 parts of lithium silicate to 80 parts of deionized water and mixing evenly to obtain a suspension;
[0044] S12, drying the suspension at 100° C., adding 20 parts of aluminum silicate and grinding thoroughly to obtain crude zinc oxide;
[0045] S13, adding 20 parts of crude zinc oxide, 2 to 5 parts of cationic starch, and 2 parts of KH550 to 40 parts of deionized water, subjecting to ultrasonic treatment at 400 W for 1.5 h, filtering, and drying to prepare pretreated zinc oxide;
[0046] S14. Mix the pretreated zinc oxide and modified glass sand in a mass ratio of 4:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 3 h, and modified calcined zinc oxide is obtained.
[0047] Preparation of high-quality marble-like ceramic glaze:
[0048] S71. By weight, 14 parts of aluminum oxide, 50 parts of silicon dioxide, 3 parts of calcium oxide, 2 parts of magnesium oxide, 0.5 parts of potassium oxide, 3 parts of sodium oxide, 1 part of boron oxide, 4 parts of barium oxide, 6 parts of strontium oxide, and 0.5 parts of calcium fluoride are fully mixed and put into a ball mill, and ground at a speed of 400 r / min for 1 hour, and then 0.5 parts of sodium tripolyphosphate and 0.5 parts of sodium silicate are added, and the speed is maintained and the grinding is continued for 6 hours, and a dry granular mixture is prepared by sieving;
[0049] S72, heating the dry granule mixture at 1500° C. to melt, then naturally cooling to room temperature, and crushing to a fineness of 350 meshes to obtain replica dry granules;
[0050] S73, according to weight, 20 parts of potassium feldspar, 2 parts of talc, 15 parts of calcined kaolin, 8 parts of modified calcined zinc oxide, 16 parts of barium carbonate, 5 parts of nepheline, 3 parts of dolomite, and 1 part of fluorite are fully mixed, and the mixture is fully ground in a ball mill at a speed of 400 r / min for 2 hours to obtain a replica slurry, and then water is added to obtain a replica glaze slurry, wherein the mass ratio of the replica slurry to water is 1:1.8;
[0051] S74. Under nitrogen conditions, stir the replica dry particles and replica glaze slurry in a mass ratio of 1:0.6 at a speed of 500 r / min for 25 minutes to obtain a mixed slurry;
[0052] S75, filtering the mixed slurry and introducing it into a ball mill for wet grinding for 50 minutes to prepare the high-quality marble replica ceramic glaze.
[0053] Example 2
[0054] The difference between Example 2 and Example 1 is that the mass ratio of the replica dry particles to the replica glaze slurry in Example 2 is 1:0.7, and the other operations are the same.
[0055] Example 3
[0056] Preparation of modified glass sand:
[0057] S31, washing the glass sand with anhydrous ethanol and drying it in a vacuum drying oven at 100°C, and then preheating it to 65°C;
[0058] S32, in parts by weight, add 8 parts of glass sand and 3 parts of carboxymethyl cellulose to 90 parts of deionized water, stir to obtain a mixed slurry, heat to 85°C, adjust the pH value of the mixed slurry to 8 with sodium hydroxide, add 8 parts of cerium sulfate, stir and mature for 1.5 hours, continue to add sodium hydroxide or potassium hydroxide to adjust the pH value of the mixed slurry to 9, maintain the temperature and mature for 2 hours, filter, wash and dry to obtain a solid;
[0059] S33, sintering the solid at 500°C for 4 hours to obtain cerium oxide-coated glass sand, and then crushing the solid to obtain modified glass sand.
[0060] Preparation of modified calcined zinc oxide:
[0061] S11, by weight, adding 35 parts of calcined zinc oxide and 25 parts of lithium silicate to 88 parts of deionized water and mixing evenly to obtain a suspension;
[0062] S12, drying the suspension at 105°C, adding 25 parts of aluminum silicate and grinding thoroughly to obtain crude zinc oxide;
[0063] S13, adding 26 parts of crude zinc oxide, 4 parts of cationic starch, and 3 parts of KH550 to 50 parts of deionized water, subjecting to 500W ultrasonic treatment for 2h, filtering, and drying to prepare pretreated zinc oxide;
[0064] S14. Mix the pretreated zinc oxide and modified glass sand in a mass ratio of 4.7:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 3 h, and modified calcined zinc oxide is obtained.
[0065] Preparation of high-quality marble-replica ceramic glaze:
[0066] S71. By weight, 16 parts of aluminum oxide, 51 parts of silicon dioxide, 5 parts of calcium oxide, 3 parts of magnesium oxide, 1 part of potassium oxide, 4 parts of sodium oxide, 1.5 parts of boron oxide, 5 parts of barium oxide, 7 parts of strontium oxide, and 0.8 parts of calcium fluoride are fully mixed and put into a ball mill, and ground at a speed of 450 r / min for 1.5 hours, and then 0.8 parts of sodium tripolyphosphate and 0.8 parts of sodium silicate are added, and the speed is maintained and the grinding is continued for 7 hours, and a dry granular mixture is prepared by sieving;
[0067] S72, heating the dry granule mixture at 1550° C. to melt, then naturally cooling to room temperature, and crushing to a fineness of 400 meshes to obtain replica dry granules;
[0068] S73. According to weight, 22 parts of potassium feldspar, 3 parts of talc, 20 parts of calcined kaolin, 10 parts of modified calcined zinc oxide, 18 parts of barium carbonate, 8 parts of nepheline, 5 parts of dolomite and 2 parts of fluorite are fully mixed, and the mixture is fully ground in a ball mill at a speed of 450 r / min for 2.5 h to obtain a replica slurry, and water is then added to obtain a replica glaze slurry, wherein the mass ratio of the replica slurry to water is 1:2;
[0069] S74. Under nitrogen conditions, stir the replica dry particles and replica glaze slurry in a mass ratio of 1:0.7 at a speed of 550 r / min for 30 minutes, and stir them thoroughly to obtain a mixed slurry;
[0070] S75, filtering the mixed slurry and introducing it into a ball mill for wet grinding for 80 minutes to prepare the high-quality marble replica ceramic glaze.
[0071] Example 4
[0072] Preparation of modified glass sand:
[0073] S31, washing the glass sand with anhydrous ethanol and drying it in a vacuum drying oven at 100°C, and then preheating it to 70°C;
[0074] S32. In parts by weight, 10 parts of glass sand and 4 parts of calcium dodecyl sulfate were added to 100 parts of deionized water, and the mixture was stirred to obtain a mixed slurry, which was heated to 90° C., the pH value of the mixed slurry was adjusted to 9 with sodium hydroxide, 10 parts of cerium sulfate were added, and the mixture was stirred and aged for 2 hours, and sodium hydroxide was continued to be added to adjust the pH value of the mixed slurry to 10, and the temperature was maintained for aging for 3 hours, and a solid was obtained by filtering, washing, and drying;
[0075] S33, sintering the solid at 600°C for 5 hours to obtain cerium oxide-coated glass sand, and then crushing the solid to obtain modified glass sand.
[0076] Preparation of modified calcined zinc oxide:
[0077] S11, by weight, adding 40 parts of calcined zinc oxide and 30 parts of lithium silicate to 100 parts of deionized water and mixing them evenly to obtain a suspension;
[0078] S12, drying the suspension at 110° C., adding 30 parts of aluminum silicate and grinding thoroughly to obtain crude zinc oxide;
[0079] S13, adding 33 parts of crude zinc oxide, 5 parts of cationic starch, and 4 parts of KH560 to 60 parts of deionized water, subjecting to 600W ultrasonic treatment for 3 hours, filtering, and drying to prepare pretreated zinc oxide;
[0080] S14. Mix the pretreated zinc oxide and modified glass sand in a mass ratio of 5.5:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 3 h, and modified calcined zinc oxide is obtained.
[0081] Preparation of high-quality marble-replica ceramic glaze:
[0082] S71. By weight, 18 parts of aluminum oxide, 53 parts of silicon dioxide, 7 parts of calcium oxide, 5 parts of magnesium oxide, 1.5 parts of potassium oxide, 5 parts of sodium oxide, 2 parts of boron oxide, 7 parts of barium oxide, 8 parts of strontium oxide, and 1 part of calcium fluoride are fully mixed and put into a ball mill, and ground at a speed of 500 r / min for 2 h, and then 1 part of sodium tripolyphosphate and 1 part of sodium silicate are added, and the speed is maintained and the grinding is continued for 8 h, and a dry granular mixture is prepared by sieving;
[0083] S72, heating the dry granule mixture at 1600° C. to melt, then naturally cooling to room temperature, and crushing to a fineness of 450 meshes to obtain replica dry granules;
[0084] S73, according to weight, 25 parts of potassium feldspar, 5 parts of talc, 25 parts of calcined kaolin, 13 parts of modified calcined zinc oxide, 21 parts of barium carbonate, 10 parts of nepheline, 6 parts of dolomite, and 3 parts of fluorite are fully mixed, and the mixture is fully ground in a ball mill at a speed of 500 r / min for 3 hours to obtain a replica slurry, and then water is added to obtain a replica glaze slurry, wherein the mass ratio of the replica slurry to water is 1:2.3;
[0085] S74. Under nitrogen conditions, stir the replica dry particles and replica glaze slurry in a mass ratio of 1:0.8 at a speed of 600 r / min for 35 minutes to obtain a mixed slurry;
[0086] S75, filtering the mixed slurry and introducing it into a ball mill for wet grinding for 100 minutes to prepare the high-quality marble replica ceramic glaze.
[0087] Comparative Example 1
[0088] The difference between Comparative Example 1 and Example 1 is that the glass sand is not modified in Comparative Example 1, and the other operations are the same.
[0089] Comparative Example 2
[0090] The difference between Comparative Example 2 and Example 1 is that the modified calcined zinc oxide in Comparative Example 2 is not treated with modified glass sand, and the other operations are the same.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 1 is that the modified calcined zinc oxide in Comparative Example 3 is not treated with a silane coupling agent, and the other operations are the same.
[0093] Comparative Example 4
[0094] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, aluminum silicate and lithium silicate are not added during the preparation of the modified calcined zinc oxide, and the other operations are the same.
[0095] Comparative Example 5
[0096] The difference between Comparative Example 5 and Example 1 is that aluminum silicate is not added during the preparation of the modified calcined zinc oxide in Comparative Example 5, and the other operations are the same.
[0097] Comparative Example 6
[0098] The difference between Comparative Example 6 and Example 1 is that the calcined zinc oxide in Comparative Example 6 is not subjected to any modification treatment, and the other operations are the same.
[0099] Performance Test:
[0100] Pour the base glaze slurry on the surface of the body. The amount of base glaze slurry is 115g / m 2, forming a bottom glaze layer, spraying ink on the bottom glaze layer according to the designed pattern requirements to obtain an effect pattern and form an ink layer; spraying the marble replica ceramic glaze prepared in the embodiment and the comparative example on the ink layer, with an amount of 95g / m 2 , forming a ceramic glaze layer to obtain a semi-finished product, firing the semi-finished product at a firing temperature of 1200°C for 45 minutes, and finally polishing to obtain a replica marble ceramic. The prepared replica marble ceramic is subjected to the following tests:
[0101] 1. Glossiness: According to GB / T 11420-2024 standard, the glossiness of the ceramic glaze surface is tested by a gloss meter;
[0102] 2. Abrasion resistance test: GB / T 3810.7-2016 "Test methods for ceramic tiles - Part 7: Determination of surface abrasion resistance of glazed tiles";
[0103] 3. Hardness test: JCT 908-2013 "Artificial Stone";
[0104] 4.Pollution resistance test: GB / T 3810.14-2016, test results are shown in Table 1:
[0105] Table 1
[0106]
[0107]
[0108] 5. Glaze surface evaluation: Sales and R&D personnel in the field of ceramics and glazes are assembled to form an evaluation team to evaluate the surface of the test samples. The evaluation results are given after discussion by the evaluation team. The evaluation content includes:
[0109] (1) Glaze touch: the evaluation team touched the glaze surface with their hands. The glaze with a touch close to natural marble was rated as excellent. The glaze was divided into three categories: inferior, medium and excellent. Among them, the glaze that was too flat and smooth (similar to glass) or obviously uneven (giving people an uncomfortable rough feeling) was rated as inferior, the glaze that was slightly rough and astringent was rated as medium, and the glaze that was smooth and delicate (similar to silk) was rated as excellent.
[0110] (2) Glaze texture performance: the evaluation team observed the glaze texture and classified the glaze as excellent if the texture and texture edge look close to natural marble. The glaze was divided into three categories: inferior, medium and excellent. Among them, the texture edge overflowed as inferior, the texture edge was clear as medium, and the texture edge transition was soft as excellent.
[0111] (3) Texture of glaze layer. The evaluation team observed the surface of the glaze layer and classified the glaze layer as having a texture close to that of natural marble as the best. The glaze layer was divided into three categories: inferior, medium and excellent. Among them, the glaze layer was whitish or turbid as inferior, the glaze layer was not whitish but not moist and slightly patinated as medium, and the glaze layer was bright in color, moist and had a patinated texture with a sense of age as excellent. The test results are shown in Table 2:
[0112] Table 2
[0113]
[0114]
[0115] As shown in Table 1 and Table 2, the marble replica ceramic glaze layer prepared by Examples 1-4 has good touch, texture performance and texture, and the wear resistance of the glaze layer reaches level 5 and the Mohs hardness reaches level 6, both of which are higher than the comparative example, indicating that the ceramic glaze prepared by the method of the present invention has good surface properties; according to Example 1 and Comparative Examples 1-2, it can be seen that the surface properties of the glaze can be effectively improved by modifying the glass sand and mixing it with zinc oxide for ball milling. According to Comparative Examples 3-6, it can be seen that the various modification treatments of zinc oxide can fully exert the role of zinc oxide, and at the same time, the dispersion of zinc oxide in the glaze is stabilized, thereby greatly improving the texture and touch of the glaze layer.
[0116] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-quality marble replica ceramic glaze, characterized in that: The method comprises a replicating dry particle and a replicating glaze slurry in a mass ratio of 1:(0.6-0.8), wherein the replicating glaze slurry is prepared by mixing the replicating slurry with water; The replica slurry comprises the following raw materials in parts by weight: 20-25 parts of potassium feldspar, 2-5 parts of talc, 15-25 parts of calcined kaolin, 8-13 parts of modified calcined zinc oxide, 16-21 parts of barium carbonate, 5-10 parts of nepheline, 3-6 parts of dolomite, and 1-3 parts of fluorite; The replica dry particles include the following raw materials in parts by weight: 14-18 parts of aluminum oxide, 50-53 parts of silicon dioxide, 3-7 parts of calcium oxide, 2-5 parts of magnesium oxide, 0.5-1.5 parts of potassium oxide, 3-5 parts of sodium oxide, 1-2 parts of boron oxide, 4-7 parts of barium oxide, 6-8 parts of strontium oxide, and 0.5-1 parts of calcium fluoride; The preparation process of the modified calcined zinc oxide is as follows: S11, by weight, adding 30-40 parts of calcined zinc oxide and 20-30 parts of lithium silicate to 80-100 parts of deionized water and mixing them evenly to obtain a suspension; S12, drying the suspension at 100-110°C, adding 20-30 parts of aluminum silicate and grinding thoroughly to obtain crude zinc oxide; S13, adding 20-33 parts of crude zinc oxide, 2-5 parts of cationic starch, and 2-4 parts of silane coupling agent to 40-60 parts of deionized water, subjecting to ultrasonic treatment at 400-600W for 1.5-3h, filtering, and drying to prepare pretreated zinc oxide; S14, mixing the pretreated zinc oxide and the modified glass sand in a mass ratio of (4-5.5):1, putting them into a ball mill for grinding, the ball mill speed is 300r / min, the grinding time is 3h, and the modified calcined zinc oxide is obtained; The preparation process of modified glass sand is as follows: S31, washing the glass sand with anhydrous ethanol and drying it in a vacuum drying oven at 100°C, and then preheating it to 60-70°C; S32. In parts by weight, 5 to 10 parts of glass sand and 2 to 4 parts of dispersant are added to 75 to 100 parts of deionized water, and the mixture is stirred to obtain a mixed slurry, which is heated to 80 to 90° C., the pH value of the mixed slurry is adjusted to 8 to 9 with alkali, 5 to 10 parts of cerium sulfate are added, and the mixture is stirred and aged for 1 to 2 hours, and the pH value of the mixed slurry is adjusted to 8 to 10 by continuing to add alkali, and the temperature is maintained for aging for 1 to 3 hours, and a solid is obtained by filtering, washing, and drying; S33, sintering the solid at 400-600°C for 3-5h to obtain cerium oxide-coated glass sand, and then crushing the solid to obtain modified glass sand.
2. The high-quality marble replica ceramic glaze according to claim 1, characterized in that: The mass ratio of the replica slurry to water is 1:(1.8-2.3).
3. The high-quality marble replica ceramic glaze according to claim 1, characterized in that: In step S13, the silane coupling agent is one of KH550, KH560 or KH570.
4. The high-quality marble replica ceramic glaze according to claim 1, characterized in that: In step S32, the dispersant is one of carboxymethyl cellulose and calcium dodecyl sulfate.
5. The high-quality marble replica ceramic glaze according to claim 1, characterized in that: In step S32, the alkali is sodium hydroxide or potassium hydroxide.
6. A method for preparing a high-quality marble replica ceramic glaze according to any one of claims 1 to 5, characterized in that: The following steps are involved: S71. According to the weight ratio of the dry granule formula, the components are fully mixed and put into a ball mill, and ground at a speed of 400-500 r / min for 1-2 hours, and then 0.5-1 parts of sodium tripolyphosphate and 0.5-1 parts of sodium silicate are added, and the speed is maintained and the grinding is continued for 6-8 hours, and the dry granule mixture is prepared by sieving; S72, heating the dry granule mixture at 1500-1600° C. to melt, then naturally cooling to room temperature, and crushing to a fineness of 350-450 meshes to obtain replica dry granules; S73, mixing the raw materials of the replica slurry according to the formula ratio, grinding them fully in a ball mill at a speed of 400-500 r / min for 2-3 hours, and then adding water to obtain a replica glaze slurry; S74, under nitrogen conditions, fully and uniformly stir the replica glaze slurry and the replica dry particles according to the mass ratio to obtain a mixed slurry; S75, filtering the mixed slurry and introducing it into a ball mill for wet grinding and ball milling to prepare the high-quality marble replica ceramic glaze.
7. The method for preparing the high-quality marble replica ceramic glaze according to claim 6, characterized in that: In step S74, the rotation speed of the sufficient stirring is 500-600 r / min, and the stirring time is 25-35 min.
8. The method for preparing the high-quality marble replica ceramic glaze according to claim 6, characterized in that: In step S75, the wet ball milling time is 50 to 100 minutes.
Citation Information
Patent Citations
Reengraved marble ceramic glaze, ceramic and preparation method
CN115872779A